Enhancer Features that Drive Formation of Transcriptional Condensates - Shrinivas, Krishna; Sabari, Benjamin R.; Coffey, Eliot L.; Klein, Isaac A.; Boija, Ann; Zamudio, Alicia V.; Schuijers, Jurian; Hannett, Nancy M.; Sharp, Phillip A.; Young, Richard A.; Chakraborty, Arup K. (Molecular cell, 2019)
Enhancers are DNA elements that are bound by transcription factors (TFs), which recruit coactivators and the transcriptional machinery to genes. Phase-separated condensates of TFs and coactivators have been implicated in assembling the transcription machinery at particular enhancers, yet the role of DNA sequence in this process has not been explored. We show that DNA sequences encoding TF binding site number, density, and affinity above sharply defined thresholds drive condensation of TFs and coactivators. A combination of specific structured (TF-DNA) and weak multivalent (TF-coactivator) interactions allows for condensates to form at particular genomic loci determined by the DNA sequence and the complement of expressed TFs. DNA features found to drive condensation promote enhancer activity and transcription in cells. Our study provides a framework to understand how the genome can scaffold transcriptional condensates at specific loci and how the universal phenomenon of phase separation might regulate this process. [Display omitted] •Transcription machinery forms condensates localized to specific DNA elements•Combination of structured and dynamic interactions enables localized condensation•DNA encoding binding site features above threshold values drive condensation•DNA features that drive condensation promote enhancer activity in cells Shrinivas et al. demonstrate that specific types of motif compositions encoded in DNA drive localized formation of transcriptional condensates. These findings explain how phase separation can occur at specific genomic locations and shed light on why only some genomic loci become highly active enhancers.